2022
DOI: 10.1111/iju.14976
|View full text |Cite
|
Sign up to set email alerts
|

Real‐world treatment patterns and oncological outcomes in early relapse and refractory disease after bacillus Calmette‐Guérin failure in non‐muscle‐invasive bladder cancer

Abstract: Objective To assess real‐world oncological outcomes between the radical cystectomy (RC) group and non‐RC group for early relapse and refractory disease. Methods We retrospectively analyzed 953 patients with recurrent non‐muscle‐invasive bladder cancer (NMIBC) who received bacillus Calmette‐Guérin (BCG) at 31 affiliated hospitals from 2000 to 2019. Patients with missing data on the timing of failure were excluded and 871 patients remained eligible, of whom 447, 357, and 67 were classified as early relapse/refra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…The latter may be a viable option for non‐cystectomy candidates or patients who outright refuse RC, not uncommon in Asian real‐world practice. However, RC should still be the first option offered, particularly given the lack of overall survival (OS) data from this study 1 . The Japan Urological Oncology Group reported poor 5‐year OS rates of 46.6% among patients with the highest‐risk status who had BCG‐unresponsive NMIBC and a pathological upstaging rate of 34% 3 …”
mentioning
confidence: 88%
See 2 more Smart Citations
“…The latter may be a viable option for non‐cystectomy candidates or patients who outright refuse RC, not uncommon in Asian real‐world practice. However, RC should still be the first option offered, particularly given the lack of overall survival (OS) data from this study 1 . The Japan Urological Oncology Group reported poor 5‐year OS rates of 46.6% among patients with the highest‐risk status who had BCG‐unresponsive NMIBC and a pathological upstaging rate of 34% 3 …”
mentioning
confidence: 88%
“…Although the EAU guidelines assert that “treatments other than RC must be considered oncologically inferior in patients with BCG‐unresponsive tumours,” this was based on Level 3 evidence. The Authors add important real‐world data reflecting current trends where bladder‐sparing options predominate 1 . This highlights an unmet need for new therapeutics and/or bladder‐sparing strategies in this group of patients.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…This study by Murakami et al examined the difference in prognosis between early relapse/refractory and intermediate/late relapse groups in NMIBC patients treated with BCG and compared the prognosis between the RC and non‐RC groups in early relapse/refractory groups 4 . Using propensity score matching, this study showed that there was no significant difference in the prognosis between the RC and non‐RC groups in early relapse/refractory NMIBC patients treated with BCG.…”
mentioning
confidence: 99%
“…Murakami et al are therefore to be congratulated for their thoroughly insight in a large study population. Real‐life data are always welcomed because they encompass a thoughtful mix of clinical guidelines and reasoning and may help physicians to counsel patients 3 …”
mentioning
confidence: 99%